Physicochemical and mineralogical properties of clays used in ceramic industry at North East Colombia (2019)
General properties of clays from Ceramica Murano Mine, in the municipality of El Zulia, Norte de Santander, have been investigated. Five clay samples were collected from different mantles of the mine. All the samples were characterized using chemical and mineralogical analysis, as well as physical properties like particle size, plasticity, drying and firing shrinkage and water absorption capacity. The chemical and mineralogical results indicated that all samples contained different amount of kaolinite and quartz, followed by hematite and anatase. Low amounts of muscovite were found mainly in samples F2 and F5. These clays are suitable for use as a raw material in creating ceramic construction products, especially for the manufacture of roof tiles and bricks according to the Winkler methodology. The variations found in the characterization of the raw material influence the technological properties of the ceramic that can be obtained from the clays under study.